(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the transformative potential of advanced computer hardware in fostering technical skills development among undergraduates in Cross River State, Nigeria. As global industries increasingly demand digitally proficient graduates, Nigerian universities face challenges such as outdated hardware, limited access to modern facilities, and inadequate technical training. Using a descriptive survey design, data were collected via questionnaires from 400 undergraduates and 80 lecturers across five public universities in Cross River State. Results indicate that only 30% of students have regular access to advanced hardware like high-performance computers, while 75% of lecturers report insufficient infrastructure to support technical skills training. However, 82% of participants believe advanced hardware, such as graphic processing units (GPUs) and virtual reality (VR) systems, could enhance skills in programming, data analysis, and engineering design. Key barriers include erratic power supply (88%) and high equipment costs (70%). The study proposes solutions like government-funded hardware upgrades and industry partnerships. Grounded in the Technology Acceptance Model (TAM), this research underscores the need for accessible, high-quality hardware to bridge the technical skills gap, preparing undergraduates for a competitive global workforce.